A 7-Year Active Surveillance Experience for Occupational Lung Cancer in Bologna, Italy (2017-2023) - Bogni, Monica; Cervino, Daniela; Rossi, Manuela R.; Galli, Paolo (La Medicina del Lavoro, 2025)
Background: In Italy, lung cancer is the second most frequent neoplasm in men and the third in women. Exposure to carcinogens in workplaces plays a significant role. Still, cases attributable to occupational exposure are currently under-reported as occupational diseases: the current National Prevention Plan also encourages active research projects for the detection of cancers attributable to occupational exposure. Methods: The Unit of Prevention and Safety in the Workplace of Bologna Local Health Authority (Azienda Unità Sanitaria Locale-AUSL-)created a network for active surveillance of occupational lung cancer cases with the dedicated Diagnostic and Therapeutic Care Pathways(PDTA). Possible occupational exposure cases were selected within all incident PDTA cases using a self-completed patient filter form. Only patients selected through the form were interviewed; occupational physicians collected personal, occupational, and clinical history. Definition of a cooperation system with the local office of the National Institute for Insurance(INAIL)for monitoring the process during the medico-legal assessments conducted by the insurance institute up to resolution. Results: 453 cases completed the filter form, 177 had a potential occupational exposure. Of these, 140 accepted the direct interview with occupational physicians. One hundred eleven cases interviewed were assessed with sure or suspect occupational origin: for 82, a claim for recognition was sent to the INAIL, while for the other 29 was sent to INAIL a report for epidemiological purposes. Out of 82 compensation claims, 18 individuals (4 females and 14 males) received compensation, while 4 cases remain under investigation. A total of 53 claims were rejected: 54.7% for lack of exposure to risk factors, 24.5% for insufficient exposure, 9.4% due to inadequate administrative documentation, 7.5% because of insufficient clinical documentation, and 3.8% for the absence of causal association. Conclusions: Several occupational lung cancers were found that otherwise would have been unrecognized. Asbestos was the most frequent agent occurring in the most widespread work sectors—construction and manufacture of metalworking products—and in the period of exposure from 1970 to 1980. Other relevant agents were welding fumes and polycyclic aromatic hydrocarbons. Active surveillance, direct patient interviews, and claims for recognition integrated by a complementary report are essential to increase the INAIL compensation rate.